2015
DOI: 10.1371/journal.pcbi.1004480
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Mixture Approach to the Study of Multistate Equilibrium: Application to Constant pH Simulation in Explicit Water

Abstract: Chemical and thermodynamic equilibrium of multiple states is a fundamental phenomenon in biology systems and has been the focus of many experimental and computational studies. This work presents a simulation method to directly study the equilibrium of multiple states. This method constructs a virtual mixture of multiple states (VMMS) to sample the conformational space of all chemical states simultaneously. The VMMS system consists of multiple subsystems, one for each state. The subsystem contains a solute and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…S4, S5, S11) and can be coupled with local structural fluctuations. The diverse timescales of these events highlight the sampling challenge associated with studying the titration of buried residues and calls for continuous development of robust enhanced sampling techniques …”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…S4, S5, S11) and can be coupled with local structural fluctuations. The diverse timescales of these events highlight the sampling challenge associated with studying the titration of buried residues and calls for continuous development of robust enhanced sampling techniques …”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Depending on the identity of the titratable group and its location, the structural perturbations during titration occur either locally on adjacent secondary structure(s) or globally, with timescales ranging from hundreds of nanoseconds to milliseconds . The diverse set of behaviors observed experimentally inspired numerous computational studies and development of novel enhanced sampling techniques . Depending on the degree of sampling, the computations, especially those based on explicit solvent simulations, met with mixed levels of successes; with progress in methodologies such as constant pH simulations coupled with pH replica exchange, encouraging agreement between computed and measured p K a values has been reported …”
Section: Introductionmentioning
confidence: 99%
“…While frequently utilized in computer aided drug design, 1214 such techniques can also be applied to a wide variety of problems including pK a predictions, 15,16 peptide binding, 17,18 and solvation free energies 19 (Figure 1). Within most free energy methods, λ is a reaction coordinate that tunes the potential between two systems of interest.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 IPS is more convenient than PME in decomposing pairwise interactions, which is essential for some new simulation methods, such as the virtual mixture of multiple states (VMMS's) method. 33 It has been demonstrated that the free energies calculated with the IPS method are consistent with that calculated with PME. 33,34 While the IPS potentials of many interaction forms have been derived, multipole interactions have not yet been explored.…”
Section: Introductionmentioning
confidence: 57%
“…33 It has been demonstrated that the free energies calculated with the IPS method are consistent with that calculated with PME. 33,34 While the IPS potentials of many interaction forms have been derived, multipole interactions have not yet been explored. It is recognized that multipoles have their advantages in describing molecular interactions.…”
Section: Introductionmentioning
confidence: 57%